Politics of Indonesia’s Soybean Policy Analysis on Roles and Interests Between Actors - Artha Yudilla (Journal of Diplomacy and International Studies, 2018)
Soybean is one of Indonesia’s most strategic foods. Thus, it’s really ironic than, that Indonesia’s local soybean production is never be able to suffice domestic demand. For decades, Indonesia has been depend on import, as the result, it threatens Indonesia food security and food sovereignty, especially when crisis happen on soybean world trade like in 2008, 2010 and 2012-2013. Ministry of agriculture always set new programs to increase the local production and achieve the goal to be self sufficient but on the other side, ministry of trade just stuck to the former program which is keep depending on import and lowering the tariff. This contradiction shows how pragmatic the soybean policy in Indonesia. The goal is only to settle the surface problem with the easiest and shortest term policy. This paper will give the analysis on how this policy happen, and why is it so difficult to change the pattern of this politic. The significance of influences and interests of each stakeholders appear to be the reason of why the policy remain incremental until today and the problem about self sufficiency and self sovereignty regarding soybean as one of the most strategic food remain unsolved.